2020
DOI: 10.3390/app10031169
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Model of Wellbore Stability of Fractured Coal Seam Considering the Effect of Cleat Filler and Analysis of Influencing Factors

Abstract: Currently, coal borehole collapses frequently occur during drilling. Considering that the coal near to the wellbore is cut into blocks, and the cleat filler of the coal influences the stress distribution near the wellbore, a new theoretical solution of a near-wellbore Stress Field in coal bed wells is established. In addition, according to the limit equilibrium theory and the E.MG-C criterion, the limit sliding formula of the quadrilateral and triangular block is deduced, and the slipping direction of the bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…The stress will affect the effect of nitrogen on fractures and macropores. Under higher stress, the closure is greater, and the stress will increase the adhesion of matrix particles and minerals in fractures and macropores, , which requires higher nitrogen pressure, and longer time will increase the connectivity. For mesopores and micropores, carbon dioxide injection will often produce carbonic acid, dissolving minerals and organic matter in the coal. ,, Conversely, nitrogen does not form an acidic residue to dissolve minerals .…”
Section: Discussionmentioning
confidence: 99%
“…The stress will affect the effect of nitrogen on fractures and macropores. Under higher stress, the closure is greater, and the stress will increase the adhesion of matrix particles and minerals in fractures and macropores, , which requires higher nitrogen pressure, and longer time will increase the connectivity. For mesopores and micropores, carbon dioxide injection will often produce carbonic acid, dissolving minerals and organic matter in the coal. ,, Conversely, nitrogen does not form an acidic residue to dissolve minerals .…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely reported that the in situ stress field (e.g., stress orientation, stress magnitude, and stress gradient) exerts complex effects on borehole stability. ,, The pressure drawdown, gas desorption-induced matrix shrinkage, and anisotropic permeability distribution during production tend to damage the borehole stability due to the stress concentration induced. ,− The impacts of mechanical properties (e.g., cohesion, friction angle, and Poisson’s ratio), which determine the strength of the coal seam on the borehole stability, were also studied . The pre-existing weak structures such as cleats/fractures and weak bedding planes around the borehole were investigated. , Some researchers conducted studies on the impact of the cleat spacing, friction angle, direction (i.e., the angle with principal stresses), and matrix shape on borehole stability. ,, Other factors like the clay content and borehole coating efficiency (the efficiency of the filter cake formed by the drilling fluid to prevent mud penetration into the formation) were also involved. , Regarding borehole parameters, the borehole inclination and azimuth angle can significantly affect its stability; ,,,,, the diameter, geometry, and depth of the borehole manifest evident impacts on collapse. , …”
Section: Wellbore Stabilitymentioning
confidence: 99%
“…The excessive dewatering rate will lead to a rapid reduction of pore pressure and soaring of the effective stress and stress concentration in the near wellbore region, producing a dynamic impulsive force and compromising the wellbore stability. The stress path in the reservoir during pressure depletion has been explored by researchers, , and various strength criteria have been employed to evaluate borehole stability, such as the Mohr–Coulomb criterion, Hoek–Brown criterion, Drucker–Prager criterion, and Mogi–Coulomb criterion. , Comparisons have been made among the criteria. Gentzis claimed that the Hoek–Brown criterion could better represent the strength of coal, while the Mohr–Coulomb criterion gives much higher strength under low-stress conditions.…”
Section: Wellbore Stabilitymentioning
confidence: 99%
“…It is found that the current research sets the shale gas reservoir and casing in full contact along the hole wellbore [19][20][21][22] and so that the partial contact is rarely studied, which is one of nonuniform loading distribution forms (in Figure 1, line AB is symmetry axis of the contact part between formation and casing). us, the variation rules of strain, deformation, and instability characteristics under nonuniform loading should be further studied.…”
Section: Introductionmentioning
confidence: 99%